2005
DOI: 10.1086/432862
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of Very Metal‐poor Stars with the Subaru High Dispersion Spectrograph. III. Light Neutron‐Capture Elements

Abstract: Elemental abundance measurements have been obtained for a sample of 18 very metal-poor stars using spectra obtained with the Subaru Telescope High Dispersion Spectrograph. Seventeen stars, among which 16 are newly analyzed in the present work, were selected from candidate metal-poor stars identified in the HK survey of Beers and colleagues. The metallicity range covered by our sample is −3.1[Fe/H] −2.4. The abundances of carbon, α-elements, and iron-peak elements determined for these stars confirm the trends f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
176
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(197 citation statements)
references
References 56 publications
18
176
3
Order By: Relevance
“…14 (Lai et al 2008;François et al 2007;Honda et al 2004;Aoki et al 2005). Similarly for the [Fe/H] > ∼ −2.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…14 (Lai et al 2008;François et al 2007;Honda et al 2004;Aoki et al 2005). Similarly for the [Fe/H] > ∼ −2.…”
Section: Discussionmentioning
confidence: 88%
“…We compare our results with high-resolution spectroscopic analyses of RGBs with [Fe/H] ≤ −2.5 in the Milky Way halo (Cayrel et al 2004;Cohen et al 2008;Aoki et al 2005Aoki et al , 2007Cohen et al 2006;Lai et al 2008;Honda et al 2004) and in faint (Ursa MajorII and Coma Berenices, Boötes I, Leo IV) and classical (Sextans, Draco, Fornax, Carina, Sculptor) dSphs (Letarte et al 2010;Shetrone et al 2001;Fulbright et al 2004;Koch et al 2008a;Cohen & Huang 2009;Aoki et al 2009;Norris et al 2010;Simon et al 2010;Frebel et al 2010b,a). We distinguish between unmixed and mixed RGBs in order to be able to draw a reliable comparison sample for the elements that are sensitive to mixing.…”
Section: Comparison Samplesmentioning
confidence: 90%
See 1 more Smart Citation
“…In all figures, the grey points show the location of RGB stars in the Milky Way halo (Honda et al 2004;Cayrel et al 2004;Spite et al 2005Spite et al , 2006Aoki et al 2005Aoki et al , 2007Cohen et al 2013Cohen et al , 2006Cohen et al , 2004Lai et al 2008;Yong et al 2013;Ishigaki et al 2013). The Sculptor stars are shown in orange.…”
Section: Comparison Samples: References Symbols and Colour Codes Inmentioning
confidence: 99%
“…Their origin has recently been under active discussion: studies of disk and halo stars by e.g. Aoki et al (2005), Mashonkina et al (2007), François et al (2007) and Montes et al (2007) found that their formation cannot be explained by a simple split into contributions from the "classical" s-process and r-process. Farouqi et al (2008b) give an average observed ratio of Sr/Y = 6.17 ± 1.06, taken from various analyses of halo stars at different metallicities and r-process enhancements.…”
Section: Heavy Elementsmentioning
confidence: 99%